Community Participation In The Si Besut 3AH Program In Kaliwungu Urban Village Jombang Regency - Asmaradani, Afifah Rania; Prathama, Ananta (UNIVERSITAS PAKUAN, 2025)
Waste problems are basically caused by unlimited human needs, which to fulfill their needs must use various sources that are not fully used. Jombang Regency is one of the regencies in East Java that always wins the Adipura award. However, based on SIPSN data in 2023, the volume of waste in Jombang Regency in 2023 reached 530.37 tons per day with the largest source of waste from households. Residents of Jombang Regency must have a sense of responsibility for the waste they produce, by managing waste from the source. Kaliwungu Urban Village has successfully implemented community-based waste management by prioritizing the 3R principles so that it is used as a pilot for the implementation of the Si BESUT 3AH program. This type of research is descriptive qualitative with the aim to analyze the participation of Kaliwungu Urban Village residents in the Si BESUT 3AH waste management program using the theory of participation forms. The data analysis technique is through data collection, data reduction, data display, and conclusion. The results showed that the residents of Kaliwungu Urban Village have contributed to the Si BESUT 3AH program from decision making on the waste management activity plan, sorting waste from home and collecting waste to the waste bank, processing recycled waste into various creations that have selling value, and providing suggestions and criticism as an evaluation of the activity, so that it can be used as a reference for residents in other areas to manage waste from the source.